Reversible magnetism switching of iron oxide nanoparticle dispersions by controlled agglomeration. Issue 10 (8th April 2021) - Müssig, Stephan; Kuttich, Björn; Fidler, Florian; Haddad, Daniel; Wintzheimer, Susanne; Kraus, Tobias; Mandel, Karl
Abstract : Defined agglomeration of iron oxide nanoparticle dispersions was induced by temperature. The changes were characterized by magnetic particle spectroscopy in situ and revealed that the agglomerates' size distribution affected magnetic properties. Abstract : The controlled agglomeration of superparamagnetic iron oxide nanoparticles (SPIONs) was used to rapidly switch their magnetic properties. Small-angle X-ray scattering (SAXS) and dynamic light scattering showed that tailored iron oxide nanoparticles with phase-changing organic ligand shells agglomerate at temperatures between 5 °C and 20 °C. We observed the concurrent change in magnetic properties using magnetic particle spectroscopy (MPS) with a temporal resolution on the order of seconds and found reversible switching of magnetic properties of SPIONs by changing their agglomeration state. The non-linear correlation between magnetization amplitude from MPS and agglomeration degree from SAXS data indicated that the agglomerates' size distribution affected magnetic properties.